Rancang Bangun Sistem Informasi Data Penjualan Motor Menggunakan Metode Object Oriented Analysis And Design Dengan UML Modelling - Arta Utama; Muhammad Luthfi Hamzah; Eki Saputra; Sutoyo Sutoyo (INTECOMS: Journal of Information Technology and Computer Science, 2020)
Human needs for technology in everyday life can not be released, almost all aspects of life can not be separated from technology. Many people use technology to facilitate their activities. This research was conducted at CV. Agus Motor which is a business engaged in the sale of used motorcycles. The system that runs on the CV. Agus Motor has several approved problems, the first is the amount of motorcycle data, customer data, and sales data that is processed using manual data such as using records on paper media or lost or scattered records. The second problem, there is no proper storage media to store these data. Problem three, there is no purchase report every month issued by employees having difficulty in providing sales results. This system is designed using HTML, PHP, CSS, and using MySQL database. The method in this study uses object-oriented analysis and design with uml modeling. system that can help in the sales process to facilitate the company such as processing data into consumer data and motorcycle sales transactions that can generate payment reports from consumers. In this payment system employees are expected to be able to input customer data, motor data, and monthly sales report scores